Reliability Analysis Between the Relationship of Entrepreneurial Competency with Human Capital Development: An Initial Survey Among Brunei Darussalam Youth Entrepreneurs - Muhammad Arsyad Hafizuddin; Muhammad Lutfi bin Abdul Lattif (International Journal of Community Service & Engagement, 2020)
Human Capital Development is a theme that is widely discussed particularly in academic, economic and development discussions. In the concept of economics, human capital sees itself as 'capital'. Thus, in the context of Brunei Darussalam, economic development especially in the field of entrepreneurship is expanding and more importantly the entrepreneurial (human capital) profession is increasingly accepted by the community especially among Brunei Darussalam youth. Therefore, this study aimed to examine the characteristics of entrepreneurship competency among youth entrepreneurs in Brunei Darussalam and to identify the relationship of entrepreneurial competence with human capital development as a preliminary study(pilot study). This study design was a quantitative study using questionnaire form modified by the researcher himself as the main instrument. The sample of this study consisted of 32 Brunei Darussalam youthentrepreneurs by purposive sampling and convenience of 17 male youth entrepreneurs and 15 female youth entrepreneurs. The data obtained will be analyzed using Statistical Package For Social Sciences (SPSS) software to gain validity and reliability of each variable construct. It is hoped that the results of this study provide some initial input on Brunei Darussalam's youth entrepreneurs as human capital in th country's development through entrepreneurship.